Understanding inflation persistence: a comparison of different models - Huw Dixon; Engin Kara (European Central Bank (ECB), 2006)
This paper adopts the Impulse-Response methodology to understand inflation persistence. It has often been argued that existing models of pricing fail to explain the persistence that we observe. We adopt a common general framework which allows for an explicit modelling of the distribution of contract lengths and for different types of price setting. In particular, we find that allowing for a distribution of contract lengths can yield a more plausible explanation of inflation persistence than indexation.
Keywords: E17; E3; 330; DGE models; inflation; Persistence; price-setting; Inflationstheorie; Vergleich; Preisrigidität; Dynamisches Gleichgewicht; Theorie